Rhetoric of Violence: A Critical Stylistic Study of Esiaba Irobi's Nwokedi - Abdurraheem, Hamzah (Silliman Journal, 2025)
Violence ruptures peaceful co-existence and communal harmony. However, some literary writers advocate violence as a panacea to addressing socio-economic inequality and leadership failure. This paper deployed critical stylistic tools of nominal groups, processes, equivalence, and contrast to explore the depth of violence in Esiaba Irobi’s Nwokedi. Data were drawn from the play, and the analysis was based on Systemic Functional Linguistics. Findings revealed that the choice of material processes bespeaks the violent ideological orientation of the youths, while the mental processes convey the mental agony suffered by the victims of violence. In addition, the use of noun modifications and equivalence provides negative descriptions and invectives that further deepen the macabre tone of violence, which gravitates towards the gruesome murder of the political leaders in the play. In conclusion, the paper explicated the functional significance of the linguistic choices that foreground the playwright's authorial style, thematic focus, and ideological orientations.